2023
DOI: 10.2196/43535
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Selected Psychological Parameters and Quality of Life of Patients With Type 1 Diabetes Mellitus Undergoing Transition From Multiple Daily Injections and Self-Monitoring of Blood Glucose Directly to the MiniMed 780G Advanced Hybrid Closed-Loop System: Post hoc Analysis of a Randomized Control Study

Abstract: Background While introducing new technologies and methods of treatment for type 1 diabetes mellitus (T1DM), it seems essential to monitor whether modern technologies in diabetes treatment may improve the psychological and emotional status of patients. Objective This study aims to assess the baseline psychological parameters of patients with T1DM during investigation of the direct transition from multiple daily injections (MDI) and self-monitoring of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…9 This adds to the growing evidence that beginning diabetes treatment with an AID system, switching from either MDI or previous generations of pump therapies, is not prohibitively burdensome and provides improvements to the user's daily experience with diabetes. [26][27][28] Patient satisfaction with the system was also reflected in the attrition rates, which mimicked those seen in the study phase. Of the 41 participants randomized to receive AID, five dropped out during the study phase (12% attrition).…”
Section: Discussionmentioning
confidence: 86%
“…9 This adds to the growing evidence that beginning diabetes treatment with an AID system, switching from either MDI or previous generations of pump therapies, is not prohibitively burdensome and provides improvements to the user's daily experience with diabetes. [26][27][28] Patient satisfaction with the system was also reflected in the attrition rates, which mimicked those seen in the study phase. Of the 41 participants randomized to receive AID, five dropped out during the study phase (12% attrition).…”
Section: Discussionmentioning
confidence: 86%
“…The patients filled out a set of questionnaires at the beginning, after 3 months ( 16 ), and after 12 months of the study. After the 3 months stage, the control group ended, and the patients from the studied group continued for an observational period of 9 months.…”
Section: Methodsmentioning
confidence: 99%
“…The trait anxiety scale assesses the tendency of the patient to react with apprehension and worry in general, and anxiety measured here is understood as a trait of personality. Each subscale consists of 20 items ( 16 , 18 ). Response for X1 assesses the intensity of current feelings evaluated by answering 1) not at all, 2) somewhat, 3) moderately so, and 4) very much so.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large retrospective study involving more than 4000 Minimed 780G users demonstrated that they achieved a mean GMI of 6.8% and a mean TIR of 76.2% after initiating AHCL, while minimizing hypoglycemia [ 22 ]. The real-world use of Minimed 780G also provides an increased level of patient satisfaction [ 23 , 24 ].…”
Section: Aid Systemsmentioning
confidence: 99%